A perspective on point-of-care tests to detect eosinophilic bronchitis. (April 2015) - Nair, Parameswaran; Zhang, Qiang; Brennan, John D.
Abstract Approximately 50% of asthma exacerbations and a third of COPD exacerbations are associated with an eosinophilic bronchitis. Quantitative cell counts reliably identify the number of eosinophils in sputum and treatment strategies that are guided by sputum eosinophil counts lead to significantly better outcomes than strategies guided by conventional assessments of symptoms and airflow. However, cell counts are not widely available and the results are not available in real time. Similarly, more sophisticated detection methods using immunoassays or genetic analysis via polymerase chain reaction are too costly and thus not amenable to rapid point-of-care diagnosis. Blood eosinophil counts and fraction of exhaled nitric oxide correlate poorly with airway eosinophilia, particularly in patients with severe airway diseases who are on corticosteroid therapy. Point of care assessments of eosinophil-specific activity may be provided by breathomics that employ metabolomics profiling of volatile compounds in breath. However, it is too early to decide if this would provide quantitative data to monitor therapy and disease activities longitudinally. Herein we provide a perspective on the potential for developing simple point-of-care tests with special emphasis on the potential for a bio-active paper diagnostic test to quantitatively assay the amount of eosinophil peroxidase in sputum samples by employing different types of detection systems.